ANALISIS FAKTOR - FAKTOR YANG MEMPENGARUHI KINERJA PEGAWAI BAGIAN MEDIS PADA UPT PUSKESMAS REMBANG 1 - Sirojul Ihsan; Anik Nurhidayati (CV. Denasya Smart Publisher, 2025)
This study aims to analyze the factors that influence the performance of medical staff at UPT Puskesmas Rembang 1. There are 3 factors analyzed including work competence, workload, and work motivation as independent variables. The population in this study was 71 medical staff. The sampling technique used was saturated sampling. The number of samples used in this study was 71 respondents. The data analysis technique used was multiple linear regression analysis. The Adjusted R Square value of 0.701 as the variability of the dependent variable, namely employee performance, can be explained by independent variables including work competence, workload, and work motivation by 70.1% while 29.9% is explained by variations in other variables not explained in this study. The results of this study indicate that work competence has a significant positive effect on the performance of medical staff, workload has a significant positive effect on the performance of medical staff, work motivation has a significant positive effect on the performance of medical staff.